Sekar Indonesia: Interactive Android-Based Learning Media for History Learning - Massaty, Muhammad Hassan; Sujana, Yudianto; Budianto, Aris (IJIE (Indonesian Journal of Informatics Education), 2017)
Historical learning in Indonesia is very minimal innovation. Due to the lack of innovation from year to year emerged various problems in historical learning activities such as monotonous, boring and uninteresting. The variety of learning media will be able to increase interest of learners in the learning process. The result of this research is an interesting and non-boring Android-based history learning media that is called Sekar Indonesia and worthy of being used as a learning media. This research method is research and development (R & D). This study was conducted using a research model developed by Borg & Gall. The research model consists of five steps: research and data collection, planning, product drafting, preliminary field testing and main product revision. Applications Sekar Indonesia tested by material experts, media experts and users. Expert testing results obtained percentage of 86.1% from material experts, 92.85% from media experts, and 97.7% form users. From the test results obtained the conclusion that the application Sekar Indonesia that has been developed can be used as a learning media.